Analysis of Pyridine, Picoline and Lutidine’s Adsorption Behavior on The Al (111)-lattice - (:unkn) unknown (AMG Transcend Association, 2021)
The reactivity and adsorption behavior of five organic inhibitors of pyridine and its derivatives of 2-picoline, 3-picoline, 4-picoline, and 2,4-lutidine at the Al(111) lattice in hydrochloric acid was studied by the principle of the HF and B3LYP level using the 6-31G and LANL2DZ basis sets from the program package gaussian 03. The compound was adsorbed on the metal lattice based on the calculated results, mainly in their protonated forms. In the Al (111)-lattice, the charge is transferred to the inhibitor, and the organic inhibitor is adsorbed at the Al (111)-lattice in an inclined state. The quantum chemical calculations of molecular reactivity show that the frontier orbitals of the four additives are distributed around the nitrogen atom of the pyridine ring, the aluminum atom of Al (111)-lattice, and active electrophilic centers are located on the nitrogen atoms of the pyridine ring. All five molecules were adsorbed with the chemical adsorption on the Al (111)-lattice, and the order of adsorption was 2-picoline>2, 4-lutidine> 4-picoline> 3-picoline> pyridine. The N atoms of four derivatives form N-Al bonds with the Al atoms of the Al (111)-lattice, which makes derivatives stably adsorb on the Al lattice.